Efecto del uso de residuo de cannabis (Cherry Oregón) sobre la calidad y producción de leche, en la alimentación de vacas Jersey - Pico Giler, Deiter Alberto (2024)
The objective of this study was to analyze the effect of using different levels of hemp rejection as a supplement in the feeding of dairy cattle, such as milk quality, milk production, presence of diarrhea in treatments, presence in a state of relaxation. The experimental design used was a completely randomized design (DCA), using 16 Jersey breed milk-producing female cattle, divided into 3 treatments and 1 control, with 3 repetitions in each with 4 experimental units for each of the repetitions. T1 with 273 grams of hemp rejection, T2 with 182 grams of hemp rejection, T3 with 91 grams of hemp rejection and the control without hemp rejection, but did consume conventional food. The milk gain per liter was taken and recorded daily individually for 16 weeks. The statistical analysis was carried out with the infoStat computer system and the Tukey test at 5%. The results obtained were the following: milk gain per liter T1: 2744 lt; T2: 2184 lt; T3: 1736 lt And T0 which is the control 1400 lt. In the examinations of urine samples taken for treatment were the following: T1 60% of CBD residues in the body, T2 81% of CBD residues in the body and T3 71% of CBD residues in the body, T0 is the witness which presents a negativity of CBD in the body.